Hyalinizing clear cell carcinoma of the soft palate: a review of literature review - Momal Tara Chand; Jacob Edens; Reynald John; Tayson Taixin Lin; Ian Jacob Anderson (University of São Paulo, 2021)
Hyalinizing clear cell carcinoma (HCCC), also known as clear cell carcinoma, not otherwise specified [CCC, (NOS)], is a rare minor salivary gland tumor characterized by proliferation of clear cells, organized in trabecular cords, or solid nests within loose to densely hyalinized stroma. It is considered a diagnosis of exclusion by the World Health Organization (WHO) because other salivary tumors may also have a clear cell component. Hence, there is a wide differential diagnosis. EWSR1-ATF1 gene rearrangements are fairly specific for this tumor, however, one of the recent studies have described its presence in clear cell odontogenic carcinoma (CCOC) one of its histologic mimickers. EWSR1 and CREM fusions have recently been described in these tumors but its importance is still not well described. Here we present a case of a 33-year-old woman who presented with a recurrent lesion of the soft palate. Her initial lesion was resected and diagnosed as low-grade myoepithelial tumor. Surgical margins at the time of initial resection were positive and the re-excision was recommended but the patient did not undergo surgery. Two years later, local recurrence at the same site was found and an excision was performed yielding negative margins. Histopathologic examination revealed features consistent with hyalinizing clear cell carcinoma. The patient remains disease free 1 year after the re-excision. The pathology, clinical characteristics, differential diagnosis and treatment of hyalinizing clear cell carcinoma are reviewed.